Pengaruh Strategi Positioning terhadap Keputusan Pembelian Produk Asuransi Jiwasraya - Sindi Sindi; Nuri Aslami (Fakultas Tarbiyah IAI Nasional Laa Roiba, 2022)
The purpose of this study is to identify and analyze the effect of product positioning strategy, price and service on consumer purchasing decisions on life insurance. This research is a library research. This research is a type of research that tries to collect data from literature studies. The first step of this research is to collect and study data from the same research by previous researchers . The results of this study indicate that products, prices and services have a significant effect on consumers' purchasing decisions on life insurance. The positioning strategy in making the decision to purchase life insurance products is positive. The company determines its target market, which includes all consumers as a whole. Meanwhile, the company's positioning strategy always prioritizes the interests of consumers, affordable product prices, and provides benefits. Keywords: Positioning strategy, Purchase decision, Influence